2015
DOI: 10.1021/nn507322y
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Exciton Diffusion in Semiconductor Nanocrystal Solids

Abstract: Colloidal nanocrystal solids represent an emerging class of functional materials that hold strong promise for device applications. The macroscopic properties of these disordered assemblies are determined by complex trajectories of exciton diffusion processes, which are still poorly understood. Owing to the lack of theoretical insight, experimental strategies for probing the exciton dynamics in quantum dot solids are in great demand. Here, we develop an experimental technique for mapping the motion of excitons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(93 citation statements)
references
References 63 publications
12
81
0
Order By: Relevance
“…It is seen that the results from the two independent best-fitting programs are in very good-to-excellent agreement. In Table 2, the best-fitted values of both D h and D s decrease monotonically with decreasing temperature, which is consistent with the multi-phonon assisted hopping mechanism [2,26,[48][49][50] and are close to the reported values [29,50] between 0.003 and 0.012 cm 2 /s for PbS CQDs which were surface passivated with different ligands. Similar to temperature-dependent electron mobility in a two-dimensional quantum dot superlattice [32] (electron mobility increase with temperature), the electron and hole mobilities, μ h and μ s , decrease monotonically with decreasing temperature, which is opposite to charge carrier mobility trends in continuous energy-band structures of e.g.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…It is seen that the results from the two independent best-fitting programs are in very good-to-excellent agreement. In Table 2, the best-fitted values of both D h and D s decrease monotonically with decreasing temperature, which is consistent with the multi-phonon assisted hopping mechanism [2,26,[48][49][50] and are close to the reported values [29,50] between 0.003 and 0.012 cm 2 /s for PbS CQDs which were surface passivated with different ligands. Similar to temperature-dependent electron mobility in a two-dimensional quantum dot superlattice [32] (electron mobility increase with temperature), the electron and hole mobilities, μ h and μ s , decrease monotonically with decreasing temperature, which is opposite to charge carrier mobility trends in continuous energy-band structures of e.g.…”
Section: Resultssupporting
confidence: 84%
“…Trial values for each parameter were selected referring to reported values for different ligand-treated PbS CQDs. Kholmicheva et al [29] studied MOA (8-mercaptooctanoic acid), and MPA (3-mercaptopropionic acid) treated PbS CQDs using photoluminescence (PL) spectroscopy, and measured the corresponding exciton diffusivities to be 0.003 cm 2 /s and 0.012 cm 2 /s, respectively. Carey et al [30] estimated free electron and hole diffusion length in the range from 30 to 230 nm for various PbS CQDs, including EDT treated, pure, CdCl 2 treated, bromide treated, pure fused, and solution or solid-state-iodidetreated PbS CQDs.…”
Section: Origins Of Anomalous Current-voltage Curvesmentioning
confidence: 99%
“…Comparable results using transient PL spectroscopy for 3-mercaptopropionic acid (MPA) ligands or 8-mercaptooctanoic acid (MOA) linked PbS CQDs were also reported elsewhere. 74 Those PbS QDs were doped with metal nanoparticles to introduce fixed exciton dissociation distances away from the location of their formation. The best-fitted separation energy ΔE between singlet and triplet states is ca.…”
Section: Resultsmentioning
confidence: 99%
“…Knowledge of photophysical processes taking place within semiconductor materials is important for developing next‐generation nanomaterial‐based assays with enormous possibilities in various applications . Among all photophysical processes studied in quantum dots (QDs), photoinduced electron transfer (PET) and Förster resonance energy transfer (FRET) have attracted intense interest from researchers . Recent developments of various FRET assays demonstrate tremendous applications of FRET mostly in biology, for example, as a spectroscopic ruler, in the development of biosensors, in vitro pH sensing, multiphoton cell imaging, determination of metabolic rates, and studying lipid rafts in cell membranes .…”
Section: Introductionmentioning
confidence: 99%